Discipline to Build Characterin Government: A Literature Review and Conceptual Analysis - Hendra Kurniawan; Emilia Rahmawati; Johannes Johannes (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research analyzes the conceptual framework of "The Discipline of Building Character" by Joseph L. Badaracco Jr., focusing on the formation of leadership character through Defining Moments. This research is motivated by a paradigm shift in leadership ethics studies, from a rule-based approach to character-based ethics or virtue ethics. The ethics paper identifies that large-scale corporate failures reflect a crisis of leadership character that requires an internal mechanism of self-reflection discipline. Badaracco argues that Defining Moments—choices between two deeply held ideals (right-versus-right)—are a laboratory for character formation that is cumulative and continuous. The research conducts a comprehensive synthesis of the contributions of ten major researchers in character ethics and moral leadership, placing Badaracco's framework in theoretical dialogue with classical virtue ethics and contemporary character development models. Defining Moments are identified through three dimensions: (1) Personal Identity ("Who Am I?"), (2) Collective Relationships ("Who Are We?"), and (3) The Social Role of Institutions ("Who Is Our Company?"). Badaracco's framework synthetically combines Aristotelian wisdom on phronesis (practical wisdom) with existential responsibility for self-creation through authentic choices. Practical implications include the institutionalization of character-based reflection processes, the design of organizations that are anti-cognitive bias, and the modeling of moral ethos by senior leadership.